Nonablative skin tightening in combination with electromyostimulation of perineal muscle in the postpartum rehabilitation - Yu.E. Dobrokhotova; T.S. Nagieva; B.A. Slobodyanyuk (LCC «Medicine-Inform», 2018)
Nonablative skin tightening in combination  with electromyostimulation of perineal muscle  in the postpartum rehabilitation Yu.E. Dobrokhotova, T.S. Nagieva, B.A. Slobodyanyuk Pirogov Russian National Medical Research University, Moscow, Russian Federation Aim: to determine the effectiveness of the use of portable electric stimulation of the perineal muscles and radiowave lifting of tissues of the vulva in the course of combined method of prevention and conservative correction of pelvic floor dysfunction (PFD) in patients in the late postpartum period. Patients and Methods: the study included 34 patients of reproductive age with initial manifestations of PFD and clinical forms of genital prolapse no higher than grade I according to POP-Q. Main group - 18 people, of which genital prolapse of grade I was detected in  6 patients. Control group - 16 people; colpoptosis of grade I was observed in 5 patients. Study methods included history taking, analysis of complaints, visual inspection of the perineum with functional tests and perineometry, vaginal-abdominal examination, laboratory examination, transvaginal and transperineal ultrasound, and a survey. Patients of the main group after preliminary training, independently carried out the training of the pelvic floor muscles using a portable electromyostimulator with a parallel course of radiowave lifting with the Surgitron™ DF® S5 (USA) device according to the Pelleve technology. Results: in patients of the main group compared to patients in the control group, according to the results of the survey, perineometry and assessment of pelvic floor muscle contraction (according to the Oxford scale), a significant decrease in PFD symptoms was manifested  (p<;0.05) against a background of the electromyostimulation in combination with perineal radiowave lifting procedures. Changes in ultrasound parameters observed during transperineal ultrasound in the main and control groups 3 months after the start of the rehabilitation program were not statistically significant. Conclusion: an effect on the tissues of the vulva and perineum using radiowave radiation of a specific spectrum with the Surgitron™ DF® S5 device accoeding to the Pelleve technology in combination with portable electromyostimulation of the pelvic floor muscles is an effective combination technique and affects at several levels: vulva and perineal tissues; striated pelvic floor muscle. Key words: pelvic floor dysfunction, vaginal relaxation syndrome, postpartum prolapse, electromyostimulation, radiowave lifting. For citation: Dobrokhotova Yu.E., Nagieva T.S., Slobodyanyuk B.A. Nonablative skin tightening in combination with electromyostimulation of perineal muscle in the postpartum rehabilitation. Russian Journal of Woman and Child Health. 2018;1(2):112-118.